TRIM21 Restricts Coxsackievirus B3 Replication, Cardiac and Pancreatic Injury via Interacting With MAVS and Positively Regulating IRF3-Mediated Type-I Interferon Production - Liu, Hui; Li, Min; Song, Yahui; Xu, Wei (Frontiers in Immunology, 2018)
Tripartite motif-containing 21 (TRIM21) is a regulator of tissue inflammation and pro-inflammatory cytokine production, and has been implicated in negative regulation ofIRF3-dependent type I interferon signaling. However, the antiviral activity of TRIM21 varies among diverse viruses and its role on regulation of type I interferon remains inconsistent in different microbial infections. Here, we investigate the potential role for TRIM21 in controlling Coxsackievirus B3 (CVB3) replication and susceptible organ pathology. We found that CVB3 infection up-regulated the expression of TRIM21 in hearts of mice and cardiomyocytes at early phase of infection. Knock-down of TRIM21 resulted in increased viral replication, while overexpression led to increased phosphorylation and dimerization of IRF3, increased IFN-β transcription and reduced viral replication in vitro. We demonstrate that TRIM21 promotes the activation of IRF3 in CVB3-infected cells via interacting with MAVS and catalyzing the K27-linked polyubiquitination of MAVS, thereby enhancing type I interferon signaling. The RING domain of ubiquitin ligase activity and PRY-SPRY domain of TRIM21 are critical for its anti-viral effect. In vivo overexpression of TRIM21 significantly protected mice against viral myocarditis by suppressing CVB3 replication and reducing cardiac inflammatory cytokine production. While TRIM21 deficient mice exhibited a decreased IFN-β production, an increased cardiac and pancreatic CVB3 replication, and aggravated pancreatic injury as well as myocarditis during acute infection. Thus, our results demonstrate TRIM21 as a positive regulator of IFN-β signaling by targeting MAVS during CVB3 infection and suggest it as a potent host defense against CVB3 infection and viral-induced injury in hearts and pancreas.